FAMILY XYLOMYIDAE - Fachin, Diego Aguilar; de Assis-Pujol, Cristiane Viera (Zootaxa, 2016)
This family is poor known in Colombia with only two known species of two genera, Solva tuberculata and Arthropeina colombiana.